ISLAMIC HYPNOTHERAPY AND ANCHOR HYPNOTHERAPY TO REDUCE SMOKING INTENTION IN ADOLESCENTS: A PILOT STUDY - Zahro Varisna Rohmadani; Ratna Yunita Setiyani Subarjo; Komarudin (al-Balagh : Jurnal Dakwah dan Komunikasi, 2022)
This study aimed to test the effectiveness of Islamic hypnotherapy and anchor technique in reducing smoking intentions in adolescents. There were 18 participants in the study: 6 people in the experimental group I (given intervention in the form of Islamic hypnotherapy), 6 people in the experimental group II (given intervention in the form of anchor hypnotherapy), and 6 people in the control group or a waiting list group which would be given intervention after the completion of intervention process in the experimental group I and II. Data were analyzed using the Wilcoxon Signed Rank Test and Kruskal Wallis Test. The data showed that Islamic hypnotherapy was effective in lowering smoking intention (p=0.027), but anchor hypnotherapy was ineffective in lowering smoking intention (p=0.343). The control group showed no change in smoking intention (p=0.596). Qualitatively, participants in experimental groups I and II reported decreased smoking frequency but the decrease was higher in the experimental group I. Meanwhile, the control group did not experience a decrease.